Macrophage membrane coated nanoparticles: a biomimetic approach for enhanced and targeted delivery. (5th February 2022) - Khatoon, Nafeesa; Zhang, Zefei; Zhou, Chunhui; Chu, Maoquan
Abstract : Macrophage membrane coated nanomaterials are used in various therapies, against infections and inflammation in order to combat immune barriers without compromising the efficacy of "cargo" molecules. Abstract : The enhanced and targeted drug delivery with low systemic toxicity and subsequent release of drugs is a major concern among researchers and pharmaceutics. In spite of greater advancement and discoveries in nanotherapeutics, the application of synthetic nanomaterials in clinics is still a challenging task due to immune barriers, limited blood circulation time, biodistribution and toxicity. In order to overcome these issues, cell membrane coated nanoparticles are widely employed for effective and targeted delivery. The macrophages have the ability to cross the physiological barriers and escape immune recognition and intracellular trafficking and have the ability to release potent pro-inflammatory cytokines, such as tumor necrosis factor (TNF) and interleukin 6 (IL-6), and therefore macrophage membrane coated nanoparticles have been exploited in the development of various therapeutics. In the present review, we have summarized the role of macrophage membranes as a coating material for the delivery of drugs to the targeted tissue in order to cure different diseases such as cancers, microbial infections, atherosclerosis and various inflammations. The review has critically analysed the latest approaches, and how to develop the macrophage membrane coated nanocarriers and their role in the improvement of the therapeutic index.